Evaluating the efficiency of state socio-economic policy of Latvia - Zhanna Tsaurkubule (Contemporary Economics, 2017)
This article presents an analytical overview and defines the essence of the concept 'social policy' in the context of its relation to the economy. The author of the article has developed a system of indicators to measure the impact of social policy and proposed a technique for assessing its efficiency on the basis of a comparative analysis of the dynamics of changes in key indicators of socio-economic development of Latvia in the context of its integration into the EU. The efficiency of social policy is determined using a system of indicators combined into eight areas of economic and social policy: social protection, employment, income, poverty, healthcare, education, demography, and economic policy. Furthermore, the authors also conducted a quantitative assessment of statistical data describing the impact of social policies, and conclusions and recommendations are drawn to improve this technique further. The research on Latvia's efficiency of social policy demonstrate that it is relatively low compared to other EU countries. In the future, it is recommended to improve the presentation of statistical data, to expand the list of indicators, and to assess the efficiency of social policy in a complex way, rather than in accordance with individual disparate indicators.
Keywords: I38; H53; P46; R13; 330; social policy; essence of social policy; social and economic development of state; indicators of social policy; efficiency of social policy; efficiency evaluation